Explaining public support for body-worn cameras in law enforcement. (1st November 2021) - Williams, Monica
ABSTRACT: Public opinion surveys have clearly demonstrated broad support for the use of body-worn cameras (BWC's) in law enforcement. Despite clear evidence of broad support, the factors that contribute to this support remain unclear. The current study uses data from a public opinion survey of policing in a mid-sized urban city to examine factors significantly related to public support for requiring police officers to wear cameras. Ordinal logistical regression analyses of the impacts of demographic and neighborhood factors, beliefs about whom BWC's protect, good and bad experiences with police, and trust in the police on support for the cameras suggest that awareness of bad experiences with the police increases support for BWC's, while believing that the cameras protect the police decreases support. These findings can inform discussions between communities and police agencies about the role of body-worn cameras in policing, particularly as they relate to the broader issues underlying the need for surveillance technologies in the first place.